Development Of Economic Learning Media Based On Video Explainer On Business Entities In The Economy In Class X Social Science 2 Man 1 Samarinda - Akhmad Irwana; Sudarman Sudarman; Riyo Riyadi (Educational Studies: Conference Series, 2021)
This research is motivated by efforts to attract students' interest in learning and make it easier for students to understand the subject matter. This study aims to develop explainer video-based economic learning media, test the feasibility level of explainer video-based learning media and find out the responses of class X social science 2 MAN 1 Samarinda students to explainer video-based economic learning media. The research method used was research and development, with the DDD-E development model and the research subjects were 34 students of class X social science 2. The instruments used in this study include a feasibility questionnaire assessed by material experts and media experts and a questionnaire on student responses to learning media. The results showed that the feasibility level of learning media based on the assessment of material experts obtained an average score of 4.73 with very good criteria, which means that the material used in the media is conveyed in a clear and structured manner that makes it easier for students to understand the material. Furthermore, the media expert's assessment obtained an average score of 4.6 with very good criteria, which means that the developed media is interesting and feasible to use because it has advantages such as animation, images and sound as well as interactive displays that make students interested in learning with explainer video media. Based on the small group trial consisting of 5 students, 2 male students and 3 female students, the percentage of this video was 92% and the results of the large group trial consisting of 34 students obtained a percentage of 86.5%, which means that this explainer video media attracts students interest in learning